2014
DOI: 10.4269/ajtmh.14-0206
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Imported Diseases in an Immigrant Population: Experience from a Teaching Hospital in Barcelona, Spain

Abstract: Abstract. The objective of this study was to describe the screening for imported diseases among an immigrant population. This retrospective observational study was of all adult immigrants attended at the Tropical Medicine Unit of the Vall d'Hebron Teaching Hospital from September of 2007 to March of 2010. The screening strategy was adjusted by symptoms, country of origin, and length of residence in Europe. Overall, 927 patients were included. The median age was 34.5 years, and 42.1% of patients were male. A di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 15 publications
2
19
2
Order By: Relevance
“…10,11,18,32 Similar to previous studies, no relationship was found between having symptoms and the presence of imported infectious diseases, suggesting that screening protocols should be carried out regardless of clinical status. 9,33 The prevalence of pathogenic infectious disease was high (73%).…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…10,11,18,32 Similar to previous studies, no relationship was found between having symptoms and the presence of imported infectious diseases, suggesting that screening protocols should be carried out regardless of clinical status. 9,33 The prevalence of pathogenic infectious disease was high (73%).…”
Section: Discussionsupporting
confidence: 66%
“…The prevalence of LTBI (61%) in this study was similar to that of other studies (46-71%), being higher than the general prevalence in the world (onethird of the world's population is estimated to be infected) and in that of other immigrant groups. [7][8][9][10]12,34 Nonetheless, the prevalence of LTBI in this study may be overestimated, since false-positive TST result may be observed in subjects who have received the Bacillus Calmette-Guérin vaccine or are infected with other mycobacterias. 12 This is important to take into account because the side effects of chemoprophylaxis for LTBI are not negligible.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations